A Comparative Study of Lipid Profile in Chronic Renal Failure Patients on Dialysis (Academia Journal of Medicine, 2018)
Background: Chronic renal failure (CRF) is characterized by irreversible destruction of nephrons along with decrease glomerular filtration  and suppressed urine. Disturbance of lipid profile in CRF has been found associated with increased triglycerides (TG) and low high density  lipids while normal level of total cholesterol (TC) and low density lipids (LDL). Dislipidemia in CRF patients induces cardiovascular diseases  (CVD); in addition, CVD in turn leads to more rapid destruction of kidney. Therefore the present study was designed to evaluate the lipid  profile in CRF patients with and without dialysis. Subjects and Methods: This was a prospective type of study conducted in the department  of medicine of a tertiary care centre. Total 100 patients of CRF patients and 40 normal control subjects were recruited for the study. CRF  patients were divided into two groups. Group I consisted CRF patients with dialysis and group II included CRF patients without dialysis.  Normal subjects were kept under group III control group. Results: Results of the present study revealed that there was a significant difference  between TG, HDL and VLDL of group I (p>0.01) and group II (p>0.01) in comparison of group III. Nevertheless, there was no significant  difference between the TC and LDL of all groups. Conclusion: CRF patients either with dialysis or without dialysis have a great possibility of  developing dyslipidemia as well as CVD. Dialysis has been found effective in reducing nitrogenous waste products in blood; however, it is not  able to decrease lipid profile in CRF patients.
Keywords: Chronic renal failure; triglycerides; CVD; dialysis